2015
DOI: 10.1007/s10571-015-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen–Glucose Deprivation (OGD) Modulates the Unfolded Protein Response (UPR) and Inflicts Autophagy in a PC12 Hypoxia Cell Line Model

Abstract: Hypoxia is the lack of sufficient oxygenation of tissue, imposing severe stress upon cells. It is a major feature of many pathological conditions such as stroke, traumatic brain injury, cerebral hemorrhage, perinatal asphyxia and can lead to cell death due to energy depletion and increased free radical generation. The present study investigates the effect of hypoxia on the unfolded protein response of the cell (UPR), utilizing a 16-h oxygen-glucose deprivation protocol (OGD) in a PC12 cell line model. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 67 publications
(73 reference statements)
0
13
0
1
Order By: Relevance
“…Discrepancies between apparently conflicting results among studies can be attributed to different experimental conditions, including the severity of the hypoxic insult, presence of reperfusion and timing of autophagy inducers or inhibitors (Vavilis et al . ). In our study, we established a 6 h OGD model without reperfusion, which resulted to about 55.1% cell survival, and administered TK during OGD.…”
Section: Discussionmentioning
confidence: 97%
“…Discrepancies between apparently conflicting results among studies can be attributed to different experimental conditions, including the severity of the hypoxic insult, presence of reperfusion and timing of autophagy inducers or inhibitors (Vavilis et al . ). In our study, we established a 6 h OGD model without reperfusion, which resulted to about 55.1% cell survival, and administered TK during OGD.…”
Section: Discussionmentioning
confidence: 97%
“…with 10% fetal bovine serum (FBS, Dojindo) was used to culture cells. The standard incubation conditions were 5% CO 2 , 37 C. The cell damage was induced by OGD for 16 h [19]. Before OGD, LBPs was administered at0, 100, 300 or 500 lg/ mL for 24 h [20].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen and glucose deprivation (OGD) of the neurons surrounding a hematoma has been considered a major factor in neuronal cell death in acute and chronic intracerebral hemorrhage (ICH) (Chien et al, 2015; Selim and Sheth, 2015; Korompoki et al, 2017). During an ICH, blood rushes into the surrounding brain tissue, at high pressure, resulting in brain damage from reduced regional cerebral blood flow in the perihematoma, and directly causing neuronal ischemia and hypoxia (Karaszewski et al, 2015; Rickards, 2015; Vavilis et al, 2015). Increasing evidences has shown that under OGD after ICH, protein misfolding and accumulation in the endoplasmic reticulum (ER) lumen initiate ER stress (Cominacini et al, 2015) and lead to mitochondrial apoptosis (Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%